Microplastic Ingestion By Zooplankton From Terengganu River Estuary To Offshore Waters - Zakaria Dauod Taha Almashaqba (Universiti Malaysia Terengganu, 2022)
Large number of plastics in various forms have been unloaded in different ecosystems; because of many improper control systems in plastic and its waste management, or incurious human behaviour. It is a matter of concern that plastics do not degrade biologically but are divided into small particles called microplastics under ultraviolet radiation or mechanical abrasion. Microplastics (<5 mm) are a common and global contaminant of aquatic ecosystems. Due to their small size, microplastic are ingested by a range of marine organisms, including zooplankton. The effect of microplastic on zooplankton and their interaction with these particles in their natural environments is still under consideration. This study presents the first report showing the microplastic ingestion by seven zooplankton taxa in the offshore waters of southern South China Sea and Terengganu River estuary as well as the extent of surface seawater contamination by microplastics. Among the zooplankton taxa groups are Calanoida, Cyclopoida, Harpacticoida, Mysids, Decapoda, Clodocera and Aphragmophora. No significant difference of ingested microplastic density among different zooplankton groups was detected between Terengganu River estuary and offshore waters. Two types of microplastic (fibres and fragments) were found in zooplankton in both study areas. The fibres were the most common type of ingested microplastic in the offshore (94%) and Terengganu River estuary (77.7%). The average sizes of ingested fibres and fragments were 361.7 ± 226.8 µm and 96.8 ± 28.1µm, respectively. Microplastic concentrations in zooplankton varied from 0.01 ± 0.002 particle/individual (Harpacticoida) to 0.2 ± 0.14 particle/individual (Aphragmophora). No significant correlation was observed between the density of the ingested microplastic and microplastic density in the surface seawater, indicating that other biotic and abiotic factors can influence the bioavailability of microplastic to zooplankton. The results provide basic information for better understanding of microplastic ingestion levels by zooplankton within Terengganu River estuary and the offshore water of southern South China Sea for future research.